Strategi Penerapan Kode Etik Jurnalistik dalam Penyajian Video di Kanal 20detik - Oktavia, Marshanda; Rusdi, Farid (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
The development of technology and information has also had an impact on the development of the world of journalism, which started from print media until now news sites, blogs and websites have emerged. With this development, we must always provide the latest innovations by providing journalistic products with different media such as via video, podcast or live broadcast. However, the media must still comply with the agreed journalistic code of ethics. This research determines the strategy for presenting videos on cyber media to comply with the journalistic code of ethics. The research uses the case study method on the